1998
DOI: 10.1007/s004660050339
|View full text |Cite
|
Sign up to set email alerts
|

Some comments on the use of radial basis functions in the dual reciprocity method

Abstract: We comment on the use of radial basis functions in the dual reciprocity method (DRM), particularly thin plate splines as used in Agnantiaris, Polyzos and Beskos (1996). We note that the omission of the linear terms could have biased the numerical results as has occurred in several previous studies. Furthermore, we show that a full understanding of the convergence behavior of the DRM requires one to consider both interpolation and BEM errors, since the latter can offset the effect of improved data approximation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…An error and convergence analysis of the DRM applied to Poisson's equation have been recently reported by Golberg et al, 24 where they observed that a full understanding of the convergence of the DRM requires one to consider both the RBFs interpolation and BEM errors.…”
Section: Basic Concepts Of the Drm-md Approachmentioning
confidence: 98%
“…An error and convergence analysis of the DRM applied to Poisson's equation have been recently reported by Golberg et al, 24 where they observed that a full understanding of the convergence of the DRM requires one to consider both the RBFs interpolation and BEM errors.…”
Section: Basic Concepts Of the Drm-md Approachmentioning
confidence: 98%
“…However, if rank de"ciency occurs for both matrices A and B, at least one diagonal entry in R will become zero, and the minimum generalized singular value will not approach zero theoretically. To examine equations (20) and (21) with equation (14), we can say that the generalized singular-value decomposition method can be used to extract the common part between two matrices as we expect in equation (14). Further, the common part, matrix P in equation (14), now is (R2W) in equations (20) and (21).…”
Section: Theorem 1 For the Helmholtz Equation Given Two Systems Havmentioning
confidence: 99%
“…Golberg et al [114] have given information on the use of RBFs in dual respiratory method (DRM), particularly in thin plates splines. They have pointed out that the omission of the linear terms could have biased the numerical results.…”
Section: Rbfns In Approximation and Interpolationmentioning
confidence: 99%